2004
DOI: 10.1128/iai.72.8.4424-4431.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Enterococcus faecalis hypR Gene Encoding a New Transcriptional Regulator on Oxidative Stress Response and Intracellular Survival within Macrophages

Abstract: In order to identify regulators of the oxidative stress response in Enterococcus faecalis, an important human pathogen, several genes annotated as coding for transcriptional regulators were inactivated by insertional mutagenesis. One mutant, affected in the ef2958 locus (designated hypR [hydrogen peroxide regulator]), appeared to be highly sensitive to oxidative challenge caused by hydrogen peroxide. Moreover, testing of the hypR mutant by using an in vivo-in vitro macrophage infection model resulted in a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 47 publications
7
86
0
Order By: Relevance
“…These findings indicate that although PerR plays a role in the virulence of E. faecalis, its involvement in the oxidative stress response of this bacterium may be different from that in B. subtilis (94). E. faecalis HypR was identified as a regulator of the oxidative stress response and as a virulence factor (533). It is a transcriptional activator of several genes during oxidative stress, including ahpCF, tpx, ef3270 (encoding a glutathione reductase), sodA, and katA (248,534).…”
Section: Oxidative Stress and Virulencementioning
confidence: 88%
See 1 more Smart Citation
“…These findings indicate that although PerR plays a role in the virulence of E. faecalis, its involvement in the oxidative stress response of this bacterium may be different from that in B. subtilis (94). E. faecalis HypR was identified as a regulator of the oxidative stress response and as a virulence factor (533). It is a transcriptional activator of several genes during oxidative stress, including ahpCF, tpx, ef3270 (encoding a glutathione reductase), sodA, and katA (248,534).…”
Section: Oxidative Stress and Virulencementioning
confidence: 88%
“…It is a transcriptional activator of several genes during oxidative stress, including ahpCF, tpx, ef3270 (encoding a glutathione reductase), sodA, and katA (248,534). An E. faecalis hypR mutant was highly sensitive to H 2 O 2 and showed a reduced ability to survive in macrophages and a decreased lethality in a mouse peritonitis model (533,534). Recent studies have shown that streptococcal genomes encode two copies of the redox-sensing Spx regulator, designated SpxA1 and SpxA2.…”
Section: Oxidative Stress and Virulencementioning
confidence: 99%
“…Several studies have shown that Ent. faecalis can survive relatively well in mouse peritoneal macrophages, whereas E. coli is rapidly killed under these conditions (Gentry-Weeks et al, 1999;Verneuil et al, 2004). This ability may play a pivotal role in infection and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hypR has been identified as the main transcriptional regulator of the oxidative stress response of Ent. faecalis, and survival of a hypR mutant is severely affected within macrophages (Verneuil et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation